Comparision protocols for extraction of microplastics in water samples - Dinh Hai, Ngoc; Duong Thanh, Nghi; Cao Thi , Thanh Nga; Le Thi, Phuong Quynh; Doan Thi , Oanh; Nguyen Trung, Kien; Duong Thi, Thuy (Vietnam Journal of Marine Science and Technology, 2023)
Microplastics (MPs) are increasingly recognized as emerging pollutants in various environmental components. However, protocols for sampling, analysis, and standardization of measurements in MPs research are still under development. The extraction method is a crucial factor that affects the accuracy and comparability of microplastic abundance data. In this study, we evaluated and compared the effectiveness of four different extraction protocols (D, MJ, MA, and S) for separating MPs from water samples of different types (brackish, marine, and river water). Known combinations of MP particles (polyethylene (PE), polyethylene terephthalate (PET), polystyrene (PS), and polyvinyl chloride (PVC)) with sizes ranging between 150 μm and 700 μm were spiked into water samples. Our results showed that the average recovery efficiency of microplastics using the four studied methods ranged from 53% to 86%. Notably, the recovery efficiency of light-density MPs was higher than that of heavy-density MPs. For purified water samples (PW) obtained from a filtration system, only H2O2 was effective in recovering MPs with an efficiency of 80 ± 6.61%. The S method for MP extraction, which combines SDS, Bioenzyme, H2O2 30%, and a saturated salt solution using NaCl, gave the highest average MP recovery of 78.13 ± 2.39% in PW and 69.72 ± 4.81% in surface water. This method has several advantages over the other three methods, such as low cost, environmental friendliness, and compatibility with various water samples, making it suitable for analyzing large amounts of MPs. Our study highlights the importance of carefully selecting the appropriate extraction protocol for accurate and reliable microplastic analysis in different water samples.